2010
DOI: 10.1039/c0cc02098b
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein in α-helical conformation at air–water interface: implication of conformation and orientation changes during its accumulation/aggregation

Abstract: a-Synuclein, a natively unstructured protein important in the neuropathology of Parkinson’s disease, was found to form a Langmuir monolayer in an a-helical conformation with its helical axis parallel to the air–water interface. This study sheds light on the role of vesicles in neuronal cells in the accumulation/aggregation of a-synuclein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…Previous work has shown that the process of nucleation of α-synuclein amyloid fibrils is likely to be heterogeneous and catalyzed by environmental features, such as air-water interfaces (26,27), lipid bilayers (28), SDS micelles and other anionic surfactants (11,29,30), or artificial interfaces such as the coatings of containers or stir bars (31). In addition, mechanical action, such as shaking and stirring, is often used to accelerate the aggregation of α-synuclein (32).…”
Section: Primary Nucleation and Fragmentation Can Be Selectively Enhamentioning
confidence: 99%
“…Previous work has shown that the process of nucleation of α-synuclein amyloid fibrils is likely to be heterogeneous and catalyzed by environmental features, such as air-water interfaces (26,27), lipid bilayers (28), SDS micelles and other anionic surfactants (11,29,30), or artificial interfaces such as the coatings of containers or stir bars (31). In addition, mechanical action, such as shaking and stirring, is often used to accelerate the aggregation of α-synuclein (32).…”
Section: Primary Nucleation and Fragmentation Can Be Selectively Enhamentioning
confidence: 99%
“…Studying Cu(II) binding by α-helical α-syn should be more biologically relevant, because α-syn is highly populated at the presynaptic termini (PST) and remains at such an interface in the α-helical conformation [19,20]. Moreover, release of metal ions by neurons during their depolarization and neurotransmission is also an interfacial process.…”
Section: Introductionmentioning
confidence: 99%
“…Typical secondary structures (also called conformations) are α−helix, β−sheets, and random coil [12][13][14]. Random coil structure is also called unstructured conformation, in which the polypeptide chain is well dissolved in the aqueous solution and moves freely in the aqueous environment.…”
Section: Background Of Peptides/proteinsmentioning
confidence: 99%
“…The technique of IRRAS for the Langmuir monolayer was developed in 1985 [33]. Subsequently, some proteins were shown to be also able to form a Lanmguir monolayer and IRRAS has been consequently used to analyze protein samples in the Langmuir monolayer [14,[34][35][36][37][38], which covers the surface of H 2 O. IRRAS can not only detect the FTIR signal of proteins, but also valuate the orientation of the proteins sample in the Langmuir monolayer due to the selection rules as discussed below [14,[34][35][36]38].…”
Section: Irras Studies Of Proteins At the Air-water Interfacementioning
confidence: 99%